Diagnostic potential of serum ACE and CBC inflammatory markers in silicosis in the ceramic workers - Akgündüz, Bilge (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
This study aims to determine whether serum sACE and CBC inflammatory markers can be used to diagnose silicosis and assess its severity. 231 subjects referred to Eskişehir City Hospital Occupational Diseases Polyclinic between January 2021 and January 2024 were examined. Groups classified into silicosis (n:131), non-silicosis (n:40), and control groups (n:40). sACE and CBC inflammatory markers were analyzed. ROC curve assessed. sACE levels were markedly elevated (85.19±36.06 U/L) in cases with higher profusion scores and disease categories compared to control and non-silicosis groups. sACE has a high diagnostic value for silicosis detection and severity assessment (AUC:0.810,p=0.001). Platelet/Lymphocyte Ratio (PLR) and Monocyte/Lymphocyte Ratio (MLR) were significant predictors of advanced silicosis with large opacities (AUC for PLR: 0.796, p=0.001; AUC for MLR: 0.726, p=0.004). Serum ACE and CBC inflammatory indices serve as valuable biomarkers for diagnosing silicosis and determining disease severity.